What evidence is there for the identification and management of frail older people in the emergency department? A systematic mapping review - Louise Preston; Duncan Chambers; Fiona Campbell; Anna Cantrell; Janette Turner; Elizabeth Goyder (National Institute for Health Research, 2018)
Background: Emergency departments (EDs) are facing unprecedented levels of demand. One of the causes of this increased demand is the ageing population. Older people represent a particular challenge to the ED as those older people who are frail will require management that considers their frailty alongside their presenting complaint. How to identify these older people as frail and how best to manage them in the ED is a major challenge for the health service to address. Objectives: To systematically map interventions to identify frail and high-risk older people in the ED and interventions to manage older people in the ED and to map the outcomes of these interventions and examine whether or not there is any evidence of the impact of these interventions on patient and health service outcomes. Design: A systematic mapping review. Setting: Evidence from developed countries on interventions delivered in the ED. Participants: Frail and high-risk older people and general populations of older people (aged > 65 years). Interventions: Interventions to identify older people who are frail or who are at high risk of adverse outcomes and to manage (frail) older people within the ED. Main outcome measures: Patient outcomes (direct and indirect) and health service outcomes. Data sources: Evidence from 103 peer-reviewed articles and conference abstracts and 17 systematic reviews published from 2005 to 2016. Review methods: A review protocol was drawn up and a systematic database search was undertaken for the years 2005-2016 (using MEDLINE, EMBASE, The Cochrane Library, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Health Management Information Consortium and PROSPERO). Studies were included according to predefined criteria. Following data extraction, evidence was classified into interventions relating to the identification of frail/high-risk older people in the ED and interventions relating to their management. A narrative synthesis of interventions/outcomes relating to these categories was undertaken. A quality assessment of individual studies was not undertaken; instead, an assessment of the overall evidence base in this area was made. Results: Of the 90 included studies, 32 focused on a frail/high-risk population and 60 focused on an older population. These studies reported on interventions to identify (n = 57) and manage (n = 53) older people. The interventions to identify frail and at-risk older people, on admission and at discharge, utilised a number of different tools. There was extensive evidence on these question-based tools, but the evidence was inconclusive and contradictory. Service delivery innovations comprised changes to staffing, infrastructure and care delivery. There was a general trend towards improved outcomes in admissions avoidance, reduced ED reattendance and improved discharge outcomes. Limitations: This review was a systematic mapping review. Some of the methods adopted differed from those used in a standard systematic review. Mapping the evidence base has led to the inclusion of a wide variety of evidence (in terms of study type and reporting quality). No recommendations on the effectiveness of specific interventions have been made as this was outside the scope of the review. Conclusions: A substantial body of evidence on interventions for frail and high-risk older people was identified and mapped. Future work: Future work in this area needs to determine why interventions work and whether or not they are feasible for the NHS and acceptable to patients. Study registration: This study is registered as PROSPERO CRD42016043260. Funding: The National Institute for Health Research Health Services and Delivery Research programme.